Constelação Bloch : viagem através de uma filosofia utópico-kairológica da história - Danilo Araujo Marques (2022)
Known in the history of western thought as the “philosopher of hope”, the German thinker Ernst Bloch (1885-1977) still seems not to have been sufficiently known by historians. This thesis aims to present the Bloch's philosophy of history based on a journey through his life and work, guided by the historian's gaze and by the sign of what we claimed as an “utopian-kairological” ethic. For this, we return to concepts and categories that underlie this conduct of those who investigate traces of the future in the “here and now”, as well as the intellectual circuit formed from it. Finally, we seek to show how Bloch himself acted in the sense of his utopian-kairological philosophy of history, by behaving as a “historian of the present” in face of two important events of the 20th century. This thesis is animated by the hypothesis that the return to the Blochian philosophy of history perhaps can offers a theoretical alternative to the crossroads of times in which we live.